1987
DOI: 10.1111/j.1365-2621.1987.tb05922.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Morphology of Oil Deposits in Some Deep Fried Products

Abstract: The distribution of oil taken up during frying was investigated in chips, snacks, and fries using red-stained oil. The effect of pre-drying using microwaving and lyophilization was also examined in chips. These studies indicated that some oil uptake occurred during frying which was not exclusively an end of frying effect. The distribution of oil depended upon the structure of the food and the ease of moisture loss. Oil uptake was influenced by slice thickness, the moisture content, its distribution and ease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 2 publications
6
30
1
1
Order By: Relevance
“…This result is in agreement with Gamble et al [13,14] and Moreira et al [24] who studied the effect of different frying temperatures on potato crisps, tortilla chips, plantain slice and plantain slices, respectively. The former found that although the early stages of frying showed the lower oil temperature resulted in lower oil content, but the overall oil content is temperature independent within the oil temperature examined.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result is in agreement with Gamble et al [13,14] and Moreira et al [24] who studied the effect of different frying temperatures on potato crisps, tortilla chips, plantain slice and plantain slices, respectively. The former found that although the early stages of frying showed the lower oil temperature resulted in lower oil content, but the overall oil content is temperature independent within the oil temperature examined.…”
Section: Introductionsupporting
confidence: 82%
“…The experimental moisture content data were most accurately fitted to an exponential function with respect to time. In contrast, a linear relationship was reported by Gamble et al [13,14] and Reddy and Dias [31] .…”
Section: Influence Of Methyl Cellulose Emulsifying Agentmentioning
confidence: 39%
“…lwt/vol. 29 (1996) No. 7 In the second fryer the ratio of concentrated indicator oil to nondyed oil was 1 to 14 so that the dye concentration after the transfer of oil with the stainless steel cup was equal to that of the dyed oil in the first experimental series.…”
Section: Preparation Of Oil Dyed With Sudan Redmentioning
confidence: 98%
“…Oil absorption has long been claimed to be a surface-related phenomenon resulting from the competition between drainage and suction into the porous crust once the food is removed from the oil bath and begins to cool (Bouchon et al, 2003;Gamble, Rice, & Selman, 1987;Moreira, Sun, & Chen, 1997). Consequently, oil absorption is heavily linked to moisture loss since it determines the extent of crust formation and therefore the volume that is available for oil infiltration.…”
Section: Oil Absorptionmentioning
confidence: 98%